Direct Power Control for AC/DC/ACConverters in Doubly Fed Induction Generators Based Wind Turbine - Abdelmalek Boulahia; Khalil NABTI; Hocine BENALLA (Institute of Advanced Engineering and Science, 2012)
In this paper direct power control (DPC) strategy is applied to control a doubly fed induction generator (DFIG) based wind energy generation system. A three level NPC ac/dc/ac converter is controlled by direct power control method. The rotor side converter is controlled by a novelle switching table based a double active power hysteresis band method. The selects appropriates voltage vector based on the instantaneous errors between the reference and estimated values of active and reactive powers and rotor flux position. Also the grid side is controlled by direct power control based a grid voltage position to ensures a constant DC voltage, Simulation results on a demonstrate robust, precise, and fast dynamic behavior of system.DOI:http://dx.doi.org/10.11591/ijece.v2i3.284